2012
DOI: 10.1007/s11999-012-2339-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Stability of Slipped Capital Femoral Epiphysis does not Correlate with Intraoperative Stability

Abstract: Background The most important objective of clinical classifications of slipped capital femoral epiphysis (SCFE) is to identify hips associated with a high risk of avascular necrosis (AVN) -so-called unstable or acute slips; however, closed surgery makes confirmation of physeal stability difficult. Performing the capital realignment procedure in SCFE treatment we observed that clinical estimation of physeal stability did not always correlate with intraoperative findings at open surgery. This motivated us to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 43 publications
1
32
1
Order By: Relevance
“…Data from a subcohort of the cohort presented here were used in prior publications. Forty of the patients were reported in earlier publications dealing with treatment results [19,30,33,36], 82 patients were used to compare clinical and intraoperative stability [35], and 13 patients were used to report early acetabular cartilage damage in SCFE [17].…”
Section: Methodsmentioning
confidence: 99%
“…Data from a subcohort of the cohort presented here were used in prior publications. Forty of the patients were reported in earlier publications dealing with treatment results [19,30,33,36], 82 patients were used to compare clinical and intraoperative stability [35], and 13 patients were used to report early acetabular cartilage damage in SCFE [17].…”
Section: Methodsmentioning
confidence: 99%
“…Ziebarth [40] found that clinical stability of SUFE as defined by Loder does not correlate with intra-operative stability. They retrospectively reviewed 82 patients with SUFE treated by open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Also, physeal stability confirmed by clinical methods did not always matched with intraoperative findings at surgery. Ziebarth et al [5] compared the clinical classifications with the intraoperative findings. Classifying SCFE by the duration of symptoms had a low specificity of 44% and a sensitivity of 82%.…”
Section: Controversies In Management Of Slipped Capital Femoral Epiphmentioning
confidence: 99%
“…Based on the eligibility to walk, the sensitivity was a low 39% and specificity was 76%. Ziebarth et al [5] concluded that the current clinical systems are not accurate to judge physeal stability in SCFE.…”
Section: Controversies In Management Of Slipped Capital Femoral Epiphmentioning
confidence: 99%